The Incorporation Of It System Of Quantity Surveying Profession - Yap, Hao Ying (2014)
The Objectives of this study are to identify the causes of delays in construction delays. Based on the literature review and survey questionnaire of this research were carry out, there are total seven categories are take part in the causes of delays in construction industry, six factors that impacts of delays in construction project and fifteen ways to mitigate the construction delays. The survey questionnaires were distributed to the targeted respondents either in consultant, contractor or client/developer type of organization. All the three objectives in this study are fully achieved. The top five important factors that are chosen by three parties involved contributed to the causes of delays are shortage of labour, rework due to errors during construction, improper construction methods implement low productivity level of labours and ineffective planning and scheduling of projects. The impacts of delays the most common are time and cost overrun. The effective ways to mitigate the delays in construction are identified by the top five consist of frequent coordination between the parties involved, site management and supervision, proper project planning and scheduling, clear information and communication channels and effective strategic planning